Biometric and physiological responses to water deficit in sugarcane at different phenological stages - Machado, Ricardo Silverio; Ribeiro, Rafael Vasconcelos; Marchiori, Paulo Eduardo Ribeiro; Machado, Daniela Favero São Pedro; Machado, Eduardo Caruso; Landell, Marcos Guimarães de Andrade (Pesquisa Agropecuaria Brasileira, 2010)
The aim of this work was to evaluate the biometric and physiological responses of sugarcane (Saccharum spp.) to water deficit (WD), during different phenological phases. Genotypes IACSP 94-2094 and IACSP 96-2042 were subjected to WD conditions during the initial, maximum and sucrose accumulation phases. The experiment was carried out in a completely randomized design. Susceptibility to WD was established by reduction in stalk dry matter and soluble solids. Water deficit reduced leaf gas exchange in all phenological phases of both genotypes. Lower plant height, less stalk dry matter and soluble solids, and reduction in number and length of internodes were only observed during the initial growth phase of the IACSP 96-2042 clone. In the initial growth phase, tolerance to WD was observed for IACSP 94-2094, with evidence of physiological acclimation, and for IACSP 96-2042 in reduction phytomass production and its soluble solid content, caused by lower stomatal conductance and lower apparent carboxylation efficiency which limit photosynthesis. Regardless of the phenological phase, genotype IACSP 94-2094 was tolerant to WD, since its phytomass production was maintained even with impairment of leaf gas exchange.